Studi empiris pengaruh peran, kinerja dan inovasi technical service perusahaan kemitraan broiler terhadap keberdayaan peternak - Ina Nurtanti; Sutrisno Hadi Purnomo; Kusnandar Kusnandar (Livestock and Animal Research, 2021)
Objective: This study aim was to analyze the influence of technical service (TS) role, performance, technical, and innovation on the broiler partnership to farmer empowerment.Methods: Sampling technique used was proportionate random sampling with 145 respondents. The analysis technique used in this study was variance-based structural equation model (SEM) or Component based SEM of Partial Least Square (PLS).Results: Based on descriptive quantification (scale Likert 1-5, very bad-very good), it was obtained that the variable role of TS had an average of 4.00 which can be interpreted that the farmers assessment to TS role is good. The TS performance variables have an average of 3.92 which mean farmers evaluated it as good enough. TS innovation variables have an average of 3.93 which means good enough. The farmer empowerment variable has an average of 3.96 which can be interpreted as good enough. Validity and reliability test results indicate the instrument is worth to use. In structural model test, the results based on R2 (0.734, 0.733 and 0.764), GoF (0.744) and Q2(0.983) show the SEM model is worth to use.Conclusions: There is a significant influence of the role, performance and innovation of TS partially on the empowerment of farmers and there is a significant influence of the role and innovation to TS performance.